2000
DOI: 10.1007/s005850050896
|View full text |Cite
|
Sign up to set email alerts
|

Statistical distributions of water content and sizes for clouds above Europe

Abstract: Abstract. The statistics of quantities involved in the synthesis of cloud scenes have been investigated from an original data base. Frequency distributions of ice and water content (IWC), horizontal and vertical sizes (L and H), and top temperatures (T) of clouds above Europe have been derived for nine types of clouds (As, Cb, Ci, Cg, LwCg, OrCg, Cs, Ns, Sc). It appears that the cumulated frequency plots can be well ®tted with log-normal or Weibull pro®les, and that for IWC and T cloud types can be split into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A method to get more detailed information on the vertical extent of these layers was described by . Using a statistical approach described by Berton (2000) to analyse ice-supersaturation layers, they showed that the thickness of ice-supersaturation layers over Lindenberg followed a Weibull distribution with different slopes for shallow and thicker layers. They also determined that the transition between the two regimes occurred around 1 km thickness.…”
Section: Vertical and Seasonal Variation Extent Of Icesupersaturationmentioning
confidence: 99%
See 1 more Smart Citation
“…A method to get more detailed information on the vertical extent of these layers was described by . Using a statistical approach described by Berton (2000) to analyse ice-supersaturation layers, they showed that the thickness of ice-supersaturation layers over Lindenberg followed a Weibull distribution with different slopes for shallow and thicker layers. They also determined that the transition between the two regimes occurred around 1 km thickness.…”
Section: Vertical and Seasonal Variation Extent Of Icesupersaturationmentioning
confidence: 99%
“…The slope of the line in this part is 0.9. For visible cirrus, the corresponding shape parameter is around 1 (Berton, 2000;Spichtinger et al, 2003). Layers less thick than 2 km probably contain data from true ice-supersaturation layers and perhaps sub-visible cirrus.…”
Section: Vertical and Seasonal Variation Extent Of Icesupersaturationmentioning
confidence: 99%